1976
DOI: 10.1677/joe.0.0680071
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Luteinizing Hormone Releasing Factor in Rat Pituitary Stalk Blood: Effects of Electrical Stimulation of the Medial Preoptic Area

Abstract: Blood was collected from the cut pituitary stalk of male and female rats before and during the application of an electrical stimulus to the medial preoptic area. The plasma was assayed for immunoreactive LH releasing factor (RF) by a double antibody radioimmunoassay using a specific antiserum raised in rabbits against the free acid derivative of the decapeptide LH-RF conjugated to bovine serum albumin. The decapeptide (used as a standard) and pituitary stalk plasma cross-reacted in a similar manner with the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…Brown-Grant & Raisman, 1972;Sawyer, 1972;van Rees, 1972;Velasco & Rothchild, 1973;Kawakami & Terasawa, 1974). Previous studies from this laboratory have shown that electrical stimulation of the medial preoptic area (Fink & Jamieson, 1976) or median eminence (Sherwood, Chiappa & Fink, 1976) is accompanied by a significant increase in the content of immunoreactive LRF in blood collected from the cut pituitary stalk of rats. The aim of the present work was to determine (1) whether stimulation of other brain areas can cause an increase or decrease in the content of LRF in pituitary stalk blood, and (2) whether other areas of the brain influence the LRF response to electrical stimulation of the medial preoptic area.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Brown-Grant & Raisman, 1972;Sawyer, 1972;van Rees, 1972;Velasco & Rothchild, 1973;Kawakami & Terasawa, 1974). Previous studies from this laboratory have shown that electrical stimulation of the medial preoptic area (Fink & Jamieson, 1976) or median eminence (Sherwood, Chiappa & Fink, 1976) is accompanied by a significant increase in the content of immunoreactive LRF in blood collected from the cut pituitary stalk of rats. The aim of the present work was to determine (1) whether stimulation of other brain areas can cause an increase or decrease in the content of LRF in pituitary stalk blood, and (2) whether other areas of the brain influence the LRF response to electrical stimulation of the medial preoptic area.…”
Section: Introductionmentioning
confidence: 90%
“…(Margate), were housed and maintained as described by Fink & Jamieson (1976). Only animals which exhibited regular 4 day oestrous cycles were used for experimentation at which time the animals weighed 200-300 g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years both in vivo (1-4) and in vitro (4)(5)(6) methods have been developed to study mechanisms of GnRH secretion directly. Direct measurement of GnRH levels in hypophyseal portal blood in vivo has been achieved by sampling from both conscious (1-3) and anaesthetized (7)(8)(9)(10)(11)(12) animals including the rat (7-lo), monkey (11. 12), sheep (1, 2) and horse (3).…”
mentioning
confidence: 99%
“…7). Local injections of oestradiol in this area initiate a signal which, when it reaches the median eminence, culminates in a surge of Gn-RH and a subsequent release of LH (Fink & Jamieson, 1976;Goodman, 1978). Interruption of this pathway by deafferentation prevented the oestradiol-positive feedback and resulted in a lack of LH surges and anovulation (Halasz & Pupp, 1969 (Krey et al, 1975;Ferin et al, 1977 (From Ferin et al, 1979.…”
Section: Gonadotrophin Release Is Pulsatilementioning
confidence: 99%